Parasocial relationships and materialism in the media: the moderating role of motivation - Woods, Emily (My University, 2023)
The literature has identified a positive relationship between materialism and social media intensity, as well as between materialism and celebrity worship. However, the literature on the relationship between materialism and parasocial relationships needs to be more thorough. Parasocial relationships are characterized by the one-sided online relationship audience members experience with media influencers, and materialism is when individuals hold values that prioritize image, popularity, making a lot of money, and having a lot of possessions. Previous studies have identified how materialism is related to the processes engaged in during extensive media consumption, as well as the attitudes involved in the increase in materialism as a function of celebrity worship, particularly envy. This study is aimed at expanding on a recently developed social comparison framework and determining whether the differing attitudes consumers hold regarding the fortunes-of-influencers (FOI) and their differing motivations behind media usage (process and social) are related to parasocial relationship intensity (PSI) and resulting materialistic outcomes. We will employ a correlational analysis using a sample of MacEwan first year students, the majority of which aged 18-24, who report frequent activity on social media, assessing the relationship between social comparison engagement, social media processes, FOI, PSI, and materialistic outcomes. The results and conclusion will be reported at a later date once the data has been collected.
Presented on April 20, 2023 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: materialism; relationships; college students; media